TINGKAT PEMAHAMAN DAN RESPONS MAHASISWA TERHADAP SOSIALISASI KEPABEANAN PROGRAM CAMPUS GOES TO CUSTOMS - Mahmudah; Finnah Fourqoniah (JOURNAL OF COMMUNITY DEDICATION, 2026)
This Community Service Activity aims to analyze the level of students’ understanding and responses toward customs socialization conducted by the Samarinda Customs Office through the Campus Goes to Customs program. The research problem is related to the limited understanding among students regarding the functions and roles of Customs in supervising the movement of goods. This study employed a quantitative approach using a descriptive method. Data were collected through questionnaires distributed to 15 students who participated in the socialization activity held on January 29, 2026, at the Samarinda Customs Office. The research instrument included indicators assessing the socialization material, the competence of the speakers, and the implementation of the activity using a rating scale from 1 to 10. The data were analyzed using descriptive quantitative analysis by calculating the average scores and the effectiveness index of the activity. The results indicate that the socialization activity achieved a very high effectiveness index of 92.53. These findings show that the material delivered, the competence of the speakers, and the implementation of the activity were rated very positively by the participants and effectively improved students’ understanding of the functions and roles of Customs as well as the importance of compliance with customs regulations.